Child Labour: Islamic Perspective - Abu Talib, M.M.; Dewan, M.H. (Universiti Teknologi Mara, 2016)
The issue of child labour got immense importance from the people around the world. Many researchers have highlighted the negative effects of hazardous child labour. However, it is also true that child labour is a common phenomenon in the developing as well as underdeveloped countries where poor families send their children to work for the economic sustenance. This article is an attempt to understand whether child labour is acceptable in the eyes of a religion – Islam. This conceptual paper makes an attempt to find solution of this ethical dilemma by analysing Islamic teachings derived from the Qur’an, the Sunnah, the comments of the Islamic scholars, and several historical evidences such as the case of the Prophet’s young companion- Anas and the case of fetus in uterus of Ghamidiyyah- the adulteress women. From the context of the economic conditions of the people of those poor Muslim countries, the issue of child labour arises as an ethical dilemma. This paper makes an attempt to provide a solution in the light of Islamic teachings. The paper concludes that Islam allows child labour that is not hazardous and unethical. In order to eliminate hazardous child labour, initiatives should be taken from four levels: individual level, family level, employment level, and state level.